2021
DOI: 10.21203/rs.3.rs-39404/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Association between air pollution in Lima and the high incidence of COVID-19: findings from a post hoc analysis.”

Abstract: Background Corona virus disease (COVID-19) originated in China in December 2019. Thereafter, a global logarithmic expansion of the cases has occurred. Some countries have a higher rate of infections despite of early implementation of quarantine. Air pollution could be related to the high susceptibility to SARS-CoV-2 and the associated case-fatality rates (deaths/cases*100). Lima, Peru has the second highest incidence of COVID-19 in Latin America, and it is also one of the cities with highest levels of air pol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
(25 reference statements)
2
9
0
Order By: Relevance
“…Interestingly, it was noticed that the link between COVID-19 and PM 2.5 could involve not only major cities, but also rural and small municipalities, where large emissions of ammonia forms (NH y ) derived from agriculture, are produced, being precursors of PM 2.5 . Similar results were also found in Peru, where Vasquez-Apestegui et al (2021) reported higher rates of COVID-19 in Metropolitan Lima, which would be attributable -among other variables-to the increased exposure to PM 2.5 in previous years. However, a post-hoc analysis of the data did not find an association with the mortality rate.…”
Section: Recent Studies By Continents and Countriessupporting
confidence: 82%
“…Interestingly, it was noticed that the link between COVID-19 and PM 2.5 could involve not only major cities, but also rural and small municipalities, where large emissions of ammonia forms (NH y ) derived from agriculture, are produced, being precursors of PM 2.5 . Similar results were also found in Peru, where Vasquez-Apestegui et al (2021) reported higher rates of COVID-19 in Metropolitan Lima, which would be attributable -among other variables-to the increased exposure to PM 2.5 in previous years. However, a post-hoc analysis of the data did not find an association with the mortality rate.…”
Section: Recent Studies By Continents and Countriessupporting
confidence: 82%
“…Besides, comparing predictors of COVID-19 cases and deaths between disproportionally Latino counties (> 17.8% Latino population) and all other counties in the USA, exposure to PM 2.5 (third vs first quartile) was significantly associated with COVID-19 related-deaths (RR: 1.230; 95%CI 1.028, 1.471) [74]. Lastly, in Latin America, data from 24 districts in Lima (Peru) showed an independent association between PM 2.5 and COVID-19 deaths per population density but not for CFR [56]. The association of long-term exposure to PM 2.5 with CFR is very uncertain: two studies of better methodological quality [56,68] indicated an unclear negative association; while two studies at high overall risk of bias [52,72] indicated positive associations of varying precision.…”
Section: Effects Of Long-term Air Pollution On Covid-19 Relateddeathsmentioning
confidence: 82%
“…A significant correlation between PM 2.5 and COVID-19 incidence was observed in Italy [66], in Lima [56] and in the Netherlands [71] but not in the US when comparing Latino vs non-Latino counties (cases: RR 1.028; 95%CI 0.918, 1.151)) [74]. However, a significant correlations between PM 2.5 , diesel PM, traffic and COVID-19 prevalence were observed in the USA [65].…”
Section: Effects Of Long-term Air Pollution On Covid-19 Susceptibilitymentioning
confidence: 93%
See 2 more Smart Citations